2001
DOI: 10.1063/1.1349083
|View full text |Cite
|
Sign up to set email alerts
|

A quantum and semiclassical study of dynamical resonances in the C+NO→CN+O reaction

Abstract: Accurate quantum mechanical reactive scattering calculations were performed for the collinear CϩNO→CNϩO reaction using a polynomial-modified London Eyring Polanyi Sato ͑PQLEPS͒ potential energy surface ͑PES͒, which has a 4.26 eV deep well in the strong interaction region, and a reference LEPS PES, which has no well in that region. The reaction probabilities obtained for both PESs show signatures for resonances. These resonances were characterized by calculating the eigenvalues and eigenvectors of the collision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Quantum effects were observed also by Abrol et al [10], who performed collinear time-independent quantum dynamics calculations on the C + NO reaction at low energies. It remains an open question as to whether quantum effects are also clearly visible in a three-dimensional treatment of the dynamics.…”
Section: Scattering Calculations On the 2 P Surfacementioning
confidence: 77%
See 2 more Smart Citations
“…Quantum effects were observed also by Abrol et al [10], who performed collinear time-independent quantum dynamics calculations on the C + NO reaction at low energies. It remains an open question as to whether quantum effects are also clearly visible in a three-dimensional treatment of the dynamics.…”
Section: Scattering Calculations On the 2 P Surfacementioning
confidence: 77%
“…It is quite feasible that the differences would then be washed out when producing cross sections by averaging the results over many values of the total angular momentum (or the impact parameter). However, Abrol et al [10] performed 2D wave packet calculations on the C + NO reaction and suggested that the resonances they observed may survive in 3D calculations. They in fact speculated that the resonances would survive in the 'real world' and it would be fascinating if this could be investigated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The fine energy grid emphasizes the resonances for E < ∼ 10 cm −1 . these shape resonances reflect the trapping of the wave-packet between the inner repulsive wall and the outer centrifugal barrier, see , Abrol et al (2001). At energies higher than about 20 cm −1 above threshold, all cross-sections become smooth functions of the energy.…”
Section: Rotational Inelastic Cross Sections With Molscatmentioning
confidence: 88%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The origin of the sharp fluctuations is rather well understood. The study of Smith life-time matrix 6,29,30 indeed reveals that fluctuations are resonance structures due to dense sets of metastable states above the dissociation limit of the intermediate complex. These structures are related to Ericson fluctuations, 31 first seen in nuclear reaction cross sections.…”
Section: Introductionmentioning
confidence: 94%